Effects of entrepreneurial competencies, knowledge management, digital marketing, entrepreneurial culture and innovation on manufacturing SME's sustainable performance - Ahmed Al Koliby, Ibraheem Saleh Mokbel (2023)
Manufacturing SMEs struggle to focus on sustainability due to limited resources and a lack of awareness and expertise. Sustainability issues are changing the business environment of manufacturing firms. Manufacturing SMEs toil with sustainability challenges due to limited resources and a lack of awareness and expertise. The objectives of this study are fourfold: to examine the effect of four factors (i.e., entrepreneurial competencies, knowledge management, digital marketing, and entrepreneurial culture) on innovation in manufacturing SMEs’ sustainable performance; to assess the effect of the four factors on sustainable performance; to examine the effect of innovation on sustainable performance; and to investigate the mediating role of innovation in the relationship between the four factors and sustainable performance. Data collected from 428 manufacturing SMEs in Malaysia were analyzed using the partial least squares-structural equation modeling (PLS-SEM) approach. The findings reveal that entrepreneurial competencies and knowledge management are the key drivers of manufacturing SMEs’ sustainable performance. Also, innovation plays a vital role in mediating the relationship between (i) entrepreneurial competencies and manufacturing SMEs’ sustainable performance, with a partially mediated effect, and (ii) two factors (i.e., digital marketing, entrepreneurial culture) and manufacturing SMEs’ sustainable performance, with fully mediated effects. Linking all factors to innovation to nurture greater agility to respond to change and market demands could strengthen manufacturing SMEs’ sustainable performance. These findings provide valuable insights for government agencies in crafting new policies to enhance Malaysian manufacturing SMEs’ sustainable performance. The study also contributes to the theory by applying the resource-based view (RBV) theory and the triple bottom line (TBL) framework as guiding principles into a unified conceptual framework. However, this study has some limitations. Future studies should be longitudinal, use multiple data sources, and include several developing countries.